2015
DOI: 10.1111/trf.13231
|View full text |Cite
|
Sign up to set email alerts
|

Extended matched intrauterine transfusions reduce maternal Duffy, Kidd, and S antibody formation

Abstract: Extended matching for all IUTs was not possible for approximately 50% of women. Strict adherence to Duffy, Kidd, and S antigens-matched IUTs decreased immunization against these antigens by 60% compared to nonmatched IUTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…In addition to fetal/maternal bleeds, 1 other trigger of RBC alloimmunization in pregnancy is intrauterine transfusion. 41 These transfusions are typically given to women in the late second or third trimesters of pregnancy if their fetus shows signs of anemia or hydrops. Given that HDFN is most often secondary to maternal alloimmunization, the pregnant women being transfused have already proven themselves to be "responders" to RBC antigens.…”
Section: Recipient Genetic Statusmentioning
confidence: 99%
“…In addition to fetal/maternal bleeds, 1 other trigger of RBC alloimmunization in pregnancy is intrauterine transfusion. 41 These transfusions are typically given to women in the late second or third trimesters of pregnancy if their fetus shows signs of anemia or hydrops. Given that HDFN is most often secondary to maternal alloimmunization, the pregnant women being transfused have already proven themselves to be "responders" to RBC antigens.…”
Section: Recipient Genetic Statusmentioning
confidence: 99%
“…Patients undergoing IUT are at higher risk of generating additional antibodies when partially matched RBCs are used, often due to limited donor supply. A recently published study by Schonewille and coworkers reported new alloantibody formation in approximately 25% of women who underwent IUT with partially matched (e.g., Rh/Kell antigen group only) RBC units. Considering these findings, it is essential that a concerted effort be made by the blood bank to provide Rh, K, Fy, Jk, and S antigen group fully phenotypically matched RBC units for IUT.…”
Section: Discussionmentioning
confidence: 99%
“…They found that it was increasingly difficult to find appropriately matched units (48% received full antigen matched, 52% received partially antigen matched), and that 4.3% of women getting high match and 11% getting moderate match formed additional antibodies 44 . Together, these data show the difficulty of prevention of alloimmunization for patients that appear to have "immune responder" characteristics.…”
Section: Accepted Manuscriptmentioning
confidence: 98%